Комп'ютерне моделювання процесу сортування порошків надтвердих матеріалів - Колодніцький, В.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
Theoretical bases of a universal method and practical ways of its application for an estimation of characteristics of quality of powders of superhard materials are stated. The computer program of an estimation strength characteristic of powders of superhard materials is created on the basis of the produced principles. Skilled check of the developed program of calculation of characteristics of strength of powders of diamond of mark АС125 by granularity 400/315.